Influence of test duration and event specialisation on oxygen uptake during simulated middle distance running - James, D.; Sandals, L.; Draper, S.; Wood, D. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Traditionally, models of determinants of middle-distance running performance have assumed that during these events oxygen uptake (VO2) reaches the maximal (VO2max) (e.g., Di Prampero et al, 1993). However, Spencer et al, (2001) found that VO2 only reached 88-94% VO2max during 800 m running. The aim of our study was to determine whether test duration or event specialism influence the VO2 attained during simulated middle-distance running. Methods Six 400 m specialists and six 800 m specialists participated in the study with personal best times within 18% and 11% of the world record respectively. The 400 m specialists completed a 400 m trial, and the 800 m specialists completed both a 400 m and 800 m trial. These trials, along with a progressive test to determine VO2max were completed in a randomised order. Oxygen uptake was determined throughout using 15 s Douglas bag collections. Oxygen uptake during the 400 m and 800 m trials was compared (paired t-test) to examine the effect of test duration in the 800 m specialists, and the VO2 during the 400 m trials between the 400 m and 800 m specialists was compared (independent samples t-test) to examine the effect of event specialism. Results A VO2 plateau was observed in all participants for the progressive test, demonstrating the attainment of VO2max. Trial duration was 55.8 ± 2.3 s and 108.4 ± 21.2 s for the 400 m and 800 m when examining the influence of test duration (in 800 m specialists). The VO2 response achieved 85.7 ± 3% and 89.1 ± 5% of VO2max for the 400 m and 800 m trials respectively (p= 0.018), and is illustrated in figure 1. Duration for the 400 m trial was 55.1 ± 4.2 s and 55.8 ± 2.3 s for the 400 m and 800 m event specialists respectively. The VO2 response achieved 93.9 ± 2% and 85.7 ± 3% of VO2max for the 400 m and 800 m specialists respectively (p = 0.001). Discussion/Conclusion These results demonstrate that whilst test duration does influence the % VO2max achieved, VO2 does not reach during the 400 m or 800 m trial. Event specialism does appear to influence the % VO2max achieved in a 400 m trial, with the 800 m specialists attaining a lower % VO2max than the 400 m specialists.